Dos espacios multiculturales de Madrid: Lavapiés y la Puerta del Sol - Peñalta Catalán, Rocío (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2010)
Madrid is a city where people from different nationalities, ethnics, languages, cultures and reli¬gions live together, that’s why we can consider it as a multicultural city. But that mixture is not equally distributed accross the urban space, but it is specially concentrated in some districts or areas. In this paper we will analyze the cases of Lavapies and Puerta del Sol.
Keywords: Madrid; Multiculturality; Lavapies; Puerta del Sol